PENGARUH CELEBRITY ENDORSER DAN IKLAN TERHADAP MINAT BELI KONSUMEN E-COMMERCE LAZADA PADA MASYARAKAT KOTA BATAM - Lee, Jess; Pitri Nainggolan, Nora (LPPM Universitas Putera Batam, 2022)
This study aims to determine and analyze the influence of celebrity endorsers and advertisements on the buying interest of Lazada e-commerce consumers in the Batam city community. In this study, there is an analytical method using quantitative analysis and analytical tools to obtain data by distributing questionnaires. In this study, a sample size of 100 respondents was analyzed to answer each questionnaire statement that had been distributed to obtain data. The data that has been obtained from distributing questionnaires is analyzed with the help of a tool, namely SPSS (Statistical Package for the Social Sciences) version 25 for multiple linear regression analysis and hypothesis testing with the aim of finding the effect of celebrity endorsers and advertisements on Lazada e-commerce consumer buying interest in the community. Batam city. The results of the t-test show that the celebrity endorser variable is 3.107>1.98472 with sig 0.002<0.05 proving that celebrity endorser has a positive and significant effect on buying interest, advertising 3.235>1.98472 with sig 0.002<0.05 proves that advertising has a positive and significant effect on buying interest. While the results of the F test show the fcount value of 24.834> 3.09 with sig 0.000 <0.05 proving that the variable (X1) celebrity endorser and variable (X2) advertising simultaneously have a positive and significant effect on the variable (Y) buying interest.